Dielectric and ferroelectric properties of lead indium niobate ceramic prepared by wolframite method - S. Wongsaenmai (2018)
The dielectric and ferroelectric properties of lead indium niobate (Pb(In1/2Nb1/2)O3, PIN) ceramic prepared by an oxide-mixing method via wolframite route were investigated. The 98.5% perovskite fine-grained PIN ceramics with average grain sizes of 1-2 μm were obtained by sintering at 1050 °C for 2 h. The dielectric properties of the PIN were of relaxor ferroelectric behavior with temperature of dielectric maximum (Tm) ∼ 53 °C and dielectric constant (εr) ∼ 4300 (at 1 kHz). The P-E hysteresis loop measurements at various temperatures showed that the ferroelectric properties of the PIN ceramic changed gradually from the paraelectric behavior at temperature above Tm to slim-loop type relaxor behavior at temperature below Tm. Moreover, the P-E loop became more open at temperatures much lower than Tm. At -25 °C, the maximum polarization is found to be 8 μm/cm2 at a field of 30 kV/cm, with Pr value of 2.5 μm/cm2 and Ec of +7.5 kV/cm. © 2007 Elsevier Ltd and Techna Group S.r.l.